Memória e violência: o conflito armado do Peru sob a ótica da literatura - Veronica Gomes Olegario Leite (2016)
This thesis focuses on the analysis of four native romances of Peru's intern conflict (1980 - 2000). It attempts to demonstrate that there are two narrative groups pleading for space in the representation among the memories during this period. The first group contemplates Rosa Cuchillo, 1996, by Óscar Colchado Lucio and Adiós Ayacucho, 1996, by Julio Ortega; the second beholds La Hora Azul, 2005, by Alonso Cueto, and Abril Rojo, 2006, by Santiago Roncagliolo. The greatest distinction between these two groups lies upon the perspective adopted at the moment of representing the conflict. Besides that, it also lies upon the assumed reader in which the literary piece aims to. The used theoretical reference presents a list of texts conveyed from the studies of the literary memory to the use of testimony. Aside from the discussions surrounding the narrative, it also identifies among other kinds of Peruvian arts, the violence presented.